Uterine Fibroid Embolization in a Series of Women Older Than 50 Years: An Observational Study - Benedetto Mondelli; Woodruff John Walker; Tanveer Dhanoya; Karen Morton (Mary Ann Liebert, 2022)
Objective: Women older than 50 years, and in particular postmenopausal, are not usually considered candidate for uterine artery embolization (UAE). We reviewed the outcome of UAE in a series of women older than 50 years, who presented with different symptoms of uterus enlargement. Population: Women referred to the radiologist from gynecologists in the United Kingdom with minimal age over 50 years. Methods: This is a retrospective observational study. The clinical criteria are women older than 50 years with symptoms related to large fibroids affecting their quality of life, who underwent UAE over a 4-year period at Royal Surrey Foundation Trust Hospital and London Clinic between 2012 and 2016. We retrieved the information from the patients' hospital notes and respective images, including magnetic resonance and ultrasound of the pelvis, and from questionnaires and telephone reviews. Main Outcome Measures: We measured the reduction of uterine size, complications, and overall satisfaction of patients. Results: The overall reduction of uterine size 8 weeks following UAE was between 50% and 64% in 12 out of 23 patients. Thirty-five percent of patients (8/23) experienced a reduction of over 65% of overall uterine volume. Only on 2 occasions, the reduction was below 50%. We asked the patients if they would recommend this operation. Twenty out of 23 would recommend it. Improvement of symptoms was measured with a scale between 0 and 5. Twelve out of 23 had total resolution of symptoms?no change in 1 case. One patient underwent a hysterectomy as symptoms persisted. Conclusions: In our series of women older than 50 years, UAE was an effective alternative to surgery, with reduction in fibroid size and improvement of symptoms.